When undone science stifles innovation: the case of the Tasmanian devil cancer. (1st September 2015) - Warren, Josephine
Abstract : Gaps or deficits in knowledge present opportunities for new and innovative research, but when studies are undone much is lost. The concept of 'undone science' can be understood within related concepts, including ignorance, nescience, non-knowledge and the chilling effect. The Tasmanian devil cancer, devil facial tumour disease (DFTD), is a new and novel cancer, potentially providing many opportunities for innovative research. The contagious cancer hypothesis for DFTD is also novel. In the research it has sponsored, the Tasmanian government elected to follow this pathway, neglecting an alternative plausible hypothesis that toxins in the devils' environment may have played a role in the initiation or progression of the cancer. The studies were not viewed as opportunities to fill gaps in devil cancer knowledge, and remain undone.